Powerful Mother (Proactive Mother Tackles Waste Burning) - Maharja, Rizky; Abdullah, Anisa Dwirizky; Panggeleng, Andi Mifta Farid (Jurnal Abmas Negeri (JAGRI), 2025)
The habit of burning waste is one of the problems caused by high household waste generation. This can be seen in Lembang Neighborhood, Lembang Village, Majene Regency, which makes burning waste an alternative for waste disposal. Therefore, the community service team conducted socialization and training to overcome this habit. The purpose of the implementation of community service was to empower women (housewives) through increasing knowledge and skills in waste management with the 3R method by selecting and sorting waste, reuse by making ecobrick, recycle by making compost through biopore absorption holes (LRB). The method used was socialization and waste management training which was evaluated through a pre-post test questionnaire sheet and a waste management observation sheet. This activity succeeded in increasing target knowledge with an achievement rate of 96,27% and increasing skills by 95%. This activity ran smoothly and achieved the achievement indicators.